2017
DOI: 10.5897/ajar2016.11737
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adoption of Improved Technologies in Rice Production in Imo State, Nigeria

Abstract: In Imo State, an increasing number of improved rice production technologies and management techniques have been introduced to rice farmers across the State. Despite the introduction of the rice production technologies, rice production continues to be low. This study therefore analyzed factors associated with adoption of improved rice production technologies in Imo State of Nigeria. Random sampling technique was used in selecting one hundred and thirty (135) rice farmers from the communities where rice is produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 17 publications
(15 reference statements)
11
23
1
Order By: Relevance
“…Farmers who have more access to extension are in a better position to access climate risk management information and improved agricultural technologies and techniques. This is in line with the findings of Ofuoku et al () and Onyeneke () on the drivers of adoption of agricultural technologies in Nigeria.…”
Section: Resultssupporting
confidence: 92%
“…Farmers who have more access to extension are in a better position to access climate risk management information and improved agricultural technologies and techniques. This is in line with the findings of Ofuoku et al () and Onyeneke () on the drivers of adoption of agricultural technologies in Nigeria.…”
Section: Resultssupporting
confidence: 92%
“…The reason for this male Yunusa (1999) and Onyeneke (2017) observed that farmers within the age bracket of 31 to 50 years are usually more innovative, motivated and adaptive individuals. The implication of this is that most of these farmers are still in their active age, and therefore have the tendency to be more productive in fish farming in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The variable off-farm income refers to the income generated by rice farmers from other sources of activities that are not related to farming. Based on the previous studies, off-farm income-generating activities increase farmers' financial capacity, resulting in a release of financial constraints [43,47]. Therefore, these farmers may deal easily with some agricultural costs compared to those who do not have off-farm income activities.…”
Section: Variables and Empirical Hypothesesmentioning
confidence: 99%